Halogen bond-assisted self-assembly of gold nanoparticles in solution and on a planar surface. Issue 39 (2nd October 2019) - Buntara Sanjeeva, Kavitha; Pigliacelli, Claudia; Gazzera, Lara; Dichiarante, Valentina; Baldelli Bombelli, Francesca; Metrangolo, Pierangelo
Abstract : Halogen bond drives the formation of AuNP chain-like and spherical structures and mediates AuNP assembly on planar surfaces. Abstract : Halogen bonding (XB) has been shown to be a powerful tool for promoting molecular self-assembly in different fields. The use of XB for noncovalent assembly of inorganic nanoparticles (NP) is, instead, quite limited, considering how extensively other interactions ( i.e., electrostatic forces, hydrophobic effect, hydrogen bonding, etc .) have been exploited to modulate and program NP self-assembly. Here, we designed and synthesized XB-capable organic ligands that were efficiently used to functionalize the surface of gold NPs (AuNPs). XB-assisted AuNP self-assembly was attained in solution mixing AuNPs bearing XB-donor ligands with ditopic XB-acceptor molecules and AuNPs functionalized with XB-acceptor moieties. Likewise, a preliminary study of XB-driven adsorption of these AuNPs on surface was performed via Quartz Crystal Microbalance with Dissipation Monitoring (QCM-D), used as an in situ tool for measuring mass changes upon XB-driven self-assembly.